THE IMPACT OF PUSH, PULL, AND MOORING TO CUSTOMER SWITCHING BEHAVIOR (CASE STUDY ON CUSTOMER INDOVISION IN MANADO) - Papalapu, Bill Jezy Nico (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Adevelopment of broadcasting business occurs very rapidly entire parts of the world. The purpose of this study is to find out the impact of push, pull, and mooring to customer switching behavior on customer of indovision in Manado. This research is causal type of research and used quantitative method. The population in this research were people living in Manado who use subscription television, especially those using Indovision and other operators in the house as well as the switch from another operator to operator Indovision. This research has used sampling technique and the sample of this research is 100 respondents. The result of this study shows that Push Pull, and Mooring have significant influence on Customer switching behavior. Indovision company must consider about the importance of satisfaction, attractive alternative and switching cost for more attention and enhanced as display quality, service and price. Keywords : Push, Pull, Mooring, Customer Switching Behavior.